2019
DOI: 10.1016/j.ibmb.2019.103247
|View full text |Cite
|
Sign up to set email alerts
|

A flavin-dependent monooxgenase confers resistance to chlorantraniliprole in the diamondback moth, Plutella xylostella

Abstract: The diamondback moth, Plutella xylostella, is a damaging pest of cruciferous crops, and has evolved resistance to many of the insecticides used for control, including members of the diamide class. Previous work on the molecular basis of resistance to diamides has documented mutations in the target-site, the ryanodine receptor, in resistant populations of P. xylostella worldwide. In contrast the role of metabolic resistance to this insecticide class is significantly less clear. Here we show that overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…A number of structurally different compounds containing a “soft nucleophile” (usually nitrogen or sulphur) that have access to the peroxyflavin intermediate are considered as potential substrates 79 , 80 . The detoxification mechanisms have been associated with the development of resistance to certain chemical pesticides including pyrethroids, pyrrolizidine alkaloids and diamides 81 83 . Both structural and physiological properties of the FMO enzyme family are still relatively unknown, except for functions in xenobiotic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A number of structurally different compounds containing a “soft nucleophile” (usually nitrogen or sulphur) that have access to the peroxyflavin intermediate are considered as potential substrates 79 , 80 . The detoxification mechanisms have been associated with the development of resistance to certain chemical pesticides including pyrethroids, pyrrolizidine alkaloids and diamides 81 83 . Both structural and physiological properties of the FMO enzyme family are still relatively unknown, except for functions in xenobiotic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorantraniliprole and other diamide insecticides have unique mechanisms and demonstrate good control of Lepidoptera pests ( Zhang et al 2014 ; Xu et al 2016 , 2017 ; He et al 2019 ), such as in DBM management ( Nauen and Steinbach 2016 ). However, the resistance of DBM to this class of insecticides has become increasingly serious ( Steinbach et al 2015 ; Liu et al 2015a , b ; Mallott et al 2019 ). This poses a challenge for the integrated management of DBM on vegetables.…”
mentioning
confidence: 99%
“…We have also previously created and performed bioassays with a transgenic fly line expressing this P450 which is included in the Fly-Tox panel. However, in our prior study this line showed no tolerance to chlorantraniliprole in the standard adult bioassay (see methods), indeed it was significantly more susceptible to this insecticide when compared to the control line lacking the transgene ( Mallott et al, 2019 ). Thus, detection of a resistance phenotype using this line with this compound may require larval bioassays to be performed.…”
Section: Resultsmentioning
confidence: 87%
“…Both RNAi knockdown and transgenic expression in D. melanogaster have provided support for a causal role of this P450 in resistance ( Li et al, 2018 ). However, in a following study, transgenic expression in Drosophila failed to confer resistance to chlorantraniliprole, with transgenic flies significantly more sensitive to this compound than a control line lacking the transgene ( Mallott et al, 2019 ). One possible explanation for this discrepancy may be differences in the bioassay methodology employed in the two studies with the former using a larval assay and the latter testing adults.…”
Section: Introductionmentioning
confidence: 99%